Effect of temperature on self-pulsation in narrow stripe, gain-guided, compact disk laser diodes - HEGARTY, JOHN (IEEE, 1998)
There is an ongoing strong interest in the development of red self-pulsating lasers for data storage compact disk (CD) applications.? Of particular importance in this mass-market application is that the laser diode emission exhibits strong self-pulsation over an extended temperature range (0-SO?C), since control of the device temperature is mitigated by the low costs required for this application.
PUBLISHED
Keywords: Physics